Revealing the metabolic characteristics of human embryonic stem cells by genome‐scale metabolic modeling. Issue 22 (2nd November 2018) - He, Yangzhige; Wang, Yan; Zhang, Boya; Li, Yang; Diao, Lihong; Lu, Liang; Yao, Jingwen; Liu, Zhongyang; Li, Dong; He, Fuchu
Abstract : Embryonic stem cells (ESCs) are characterized by a dual capacity, self‐renewal and pluripotency, which can be regulated by metabolism. A better understanding of ESC metabolism and regulatory mechanisms is pivotal for research into development, ageing, and cancer treatment. However, a systematic and comprehensive delineation of human ESC metabolism is still lacking. Here, we reconstructed the first genome‐scale metabolic model (GEM) of human ESCs (hESCs). By GEM simulation and analyses, hESC global metabolic characteristics including essential metabolites and network motifs were identified. Potential metabolic subsystems responsible for self‐renewal and pluripotency were also identified by analyses and experiments. This first GEM of hESCs provides a novel view and resource for stem cell metabolism research and will contribute to the elucidation of their metabolic characteristics. Abstract :